Handbook of Electric Power Calculations - Beaty, H. Wayne; Santoso, Surya (2015)
Fully revised to include calculations needed for the latest technologies, this essential tool for electrical engineers and technicians provides the step-by-step procedures required to solve a wide array of electric power problems.